Barriers to mammography among women attending gynecologic outpatient clinics in Tehran, Iran - Ahmadian, Maryam; Abu Samah, Asnarulkhadi; Redzuan, Ma'rof; Emby, Zahid (Academic Journals, 2011)
The aim of this study was to understand barriers to mammography among women attending obstetric and gynecologic outpatient clinics. Women at 4 obstetric and gynecologic clinics affiliated to Tehran University of Medical Sciences in Tehran were invited to participate in a cross-sectional survey with self-administered questionnaire and divided into two groups. The participant group consisted of women who had mammogram in the last two years and the non-participant group of women who had never had mammogram or for whom it had been over 2 years since their last mammogram. A total of 400 women aged 35 to 69 years, were randomly selected using random cluster sampling: 86(21.5%) were evaluated as the participant group and 314(78.5%) as the non-participant group. The result showed that lack of doctors’ advice, for the participant group, and embarrassment, for the non-participant group, are the most salient barriers. Mammography screening remains a health challenge for women and results suggest a comprehensive approach to focus on the attitudinal and logistic barriers.